Autologous Micrograft Technology (AMT) and Finasteride for the Management of Androgenic Alopecia – A Systematic Review and Meta-analysis of the Efficacy and Safety - Ellerby, Adam; Knudsen, Russell (Dermatology Practical & Conceptual, 2026)
Introduction: Present treatment methods for the management of androgenetic alopecia (AGA) have shortcomings. Though recent studies suggest that autologous micrograft technology (AMT) may be an effective alternative, smaller samples sizes in these studies calls for using statistical methods to get pooled effect sizes. Objectives: To compare the efficacy of AMT and finasteride in the management of AGA, using a meta-analysis study, comparators being hair count and percentage of patients benefitted from the treatment. Methods: A systematic review and meta-analysis was performed, using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The protocol was registered in PROSPERO (Reg. No: CRD42024578804). Databases searched for potential articles includes: PubMed, ScienceDirect, CINAHL, Cochrane, MEDLINE-OVID, Embase-OVID, Web of Science Core Collection, and Bielefeld Academic Search Engine. Results: This study suggest that AMT treatment may be superior to ≥1mg/day finasteride for the management of AGA. With regards to improvement in hair count, both AMT (Hedges’s g = 0.324, 95% CI: 0.198 – 0.450; p<0.001) and finasteride (Hedges’s g = 0.251, 95% CI: 0.153 – 0.349; p<0.001) showed small effect sizes. When the percentage of patients benefitted is considered, AMT had a medium effect size (Hedges’s g = 0.634, 95% CI: 0.372 – 0.896; Z-value = 4.736; p<0.001) whereas finasteride had a small effect size (Hedges’s g = 0.201, 95% CI: 0.153 – 0.248; p<0.001). Conclusion: This study suggests that AMT is an effective method for promoting hair growth in patients with AGA and presents evidence for the superiority of AMT over finasteride.